Plant-cyanobacteria Interaction: Phytotoxicity of Cyanotoxins - Gogoi; Lokendra Singh, Jubilee Purkayastha*, Hemanta Kumar (Journal of Phytology, 2010)
Cyanobacteria from freshwater and also from marine sources produce a wide array of toxic chemicals and secondary or bioactive metabolites. These are mainly nitrogen-rich alkaloids and peptides and are now identified as to pose threats both to human and environmental health as well as on aquatic and terrestrial plants. Irrigation of edible plants with Cyanobacteria containing water may pose threat of indirect exposure of human health to cyanotoxins via bio-accumulation of these toxins in plant tissues. Moreover, Cyanotoxins have been shown to inhibit plant growth and development. It has also been suggested that some of the compounds may have ecological roles as allelochemicals and can be used as potential biocides and even to combat malignant cells.Â In this review, we highlight the different naturally occurring Cyanobacterial toxins popularly known as cyanotoxins and their interaction with plants with special emphasis on phytotoxic effects of cyanotoxins. Also, existing evidence for the positive taxis of plant-cyanobacteria interaction and potential for development and application of bioactive molecules from Cyanobacterial toxins are highlited. Key words: Cyanobacteria, toxins, phytotoxicity, allelopathy, biocide <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Jubilee Purkayastha. Plant-cyanobacteria Interaction: Phytotoxicity of Cyanotoxins. Â J Phytol 2/7 (2010) 07-15.